Corruption Disclosure: Can Evidence Competence Intervene In The Impact Of Forensic Auditor Professionalism And Expertise? - Reschiwati Reschiwati; Nasrullah Nasrullah; Amrizal Amrizal (Universitas Muhammadiyah Malang, 2022)
This study aims to examine the effect of the professionalism and expertise of forensic auditors on corruption disclosure with evidence competence as an intervening variable. Respondents in this study were forensic auditors at the Main Examiner of State Finance I BPK RI and the Deputy for Investigation at the DKI Jakarta Province BPKP Representative. The sample selection used the convenience method . The research instrument is a questionnaire. The number of answers that can be processed is as much as 80 respondents. The data analysis method was Partial Least Square. The results of the study show that the professionalism and expertise of the forensic auditor influences both the competence of evidence and the disclosure of corruption. Evidence competency influences disclosure of corruption and is proven to be able to intervene both the professional influence of the forensic auditor and the influence of the forensic auditor's expertise on corruption disclosure. This study has implications that the forensic auditor in carrying out audit procedures cannot be separated from the professionalism and expertise possessed. The auditor must produce competent audit evidence to give investigators confidence about witness testimony, expert testimony, letters, instructions, and defendant statements.